Mediatised Culturalisation Through Television: Second-Generation Alevi Kurds in London - Emre Cetin, Kumru Berfin (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Satellite television has not only provided migrant communities with stronger ties to their home countries but also enabled second-generation migrants in particular to know more about their country of origin beyond their family ties. The aim of this chapter is to explore the ways in which Turkish television contributes towards the making of the transnational identity of the “twice minority” group of Alevi Kurds through what I call mediatised culturalisation. Drawing on 17 in-depth interviews that I conducted with the second-generation members of the Alevi Kurdish community in London in 2016, I explore the role of Turkish television in contesting the boundaries of transnational social imaginaries of the second-generation viewers.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Royaume-Uni (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

Revisiting the Unplugged Margins: Rural Television Audiences and Mediatization - Türkoğlu, Nurçay (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter examines the social transformation of the television audience of rural Turkey. Villages near a metropolitan area, which were subject to an administrative decision to be relocated, were the focus of my fieldwork 30 years ago. Several visits between 1987 and 2019 to the same location, which is inhabited by television viewers and non-viewers alike, yielded an insightful mapping of engagement with popular culture via television at the periphery in Turkey from a historical perspective. While rural inhabitants are busy with daily labor in the countryside and are not keen on watching television, they are nonetheless aware of and connected to new, nationwide cultural trends and social changes. By reflexively discussing these experiences in ethnographic fieldwork on television habits and reception in rural Turkey over a 30-year span, I avoid the traps of modern-traditional and urban-rural binaries, allowing for an exploration of the role of television in mediating social change in the rural context and thus an analysis of the various complex layers and processes of mediatization among rural audiences.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Le soft power à l’épreuve de la réception. Le cas des fictions sérielles turques en Grèce - Larochelle, Dimitra Laurence (Réseaux, 2021)
La production de fictions sérielles turques est en constant développement. Ces fictions ont un très grand succès au niveau local (Tanriöver, 2011 ; Öztürkmen, 2018), avant d’être exportées au-delà des frontières turques depuis les années 2000, d’abord dans des pays sous l’influence culturelle de l’ancien Empire ottoman (à savoir les Balkans et le Moyen-Orient, puis au-delà (en Amérique latine, en Chine, au Pakistan, en Inde, au Bangladesh, etc.), faisant de la Turquie un leader mondial en matière de production et d’exportation. La Grèce est devenue un grand consommateur de fictions sérielles turques et les forts taux d’audience que ces dernières y réalisent ont conduit certains chercheurs à débattre du soft power turc. Plus précisément, en se basant sur les activités des fans des feuilletons en question (comme le tourisme en direction de la Turquie), certains ont soutenu que le visionnage des feuilletons turcs entraîne une amélioration des relations gréco-turques (Paris, 2013). En parallèle, de nombreux articles journalistiques, aussi bien en Grèce que dans d’autres pays, analysent le succès de ces feuilletons auprès du public grec comme une réussite diplomatique du gouvernement turc (Moore, 2013 ; Dimitrakopoulos, 2020).
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; France (lieu de production du savoir); Grèce (corpus analysé); Turquie (corpus analysé); _Nettoyé